A Case Report of Ovarian Fibrothecoma in a Premenopausal Women with Recurrent Menorrhagia - Rexhepi, Meral; Trajkovska, Elizabeta; Ismaili, Hysni; Azemi, Majlinda (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Ovarian fibrothecoma is a rare, benign, sex cord-stromal neoplasm, with a typically unilateral location in the ovary, characterized by mixed features of both fibroma and thecoma. Ovarian fibrothecoma is uncommon tumor of gonadal stromal cell origin accounting for 3-4% of all ovarian tumours. CASE PRESENTATION: We presented a rare case of a 46-year-old patient with recurrent menorrhagia in the past two years with no previous medical, surgical or gynecological history. She underwent two times curettage procedures. At the admission to hospital ultrasonography showed a homogenous solid right ovarian mass of size 2.5 cm x 3.5 cm. Endometrial curettage revealed simple hyperplasia of the endometrium. Diagnostic evaluation and surgical management are discussed along with a brief review of the literature. Total abdominal hysterectomy with bilateral salpingo-oophorectomy was carried out. Histopathology confirmed fibrothecoma of the ovary, proliferative endometrium with hyperplasia without atypia and multiple uterine fibroids. CONCLUSION: In all patients presenting with recurrent menorrhagia and adnexal tumor the possibility of a granulosa cell tumor must be kept in mind during evaluation.